Answer:
-52, -69, -89, -100, -124
Step-by-step explanation:
When your dealing with negative numbers the smaller number the larger it is.
Hope this helps have a nice day:)
Note:
Answer:
Answer:
To factor the expression 27x^3 - 1 using the difference of cubes formula, we can follow these steps:
1. Identify the cube root of each term. In this case, the cube root of 27x^3 is 3x, and the cube root of 1 is 1.
2. Write the formula for the difference of cubes, which is: a^3 - b^3 = (a - b)(a^2 + ab + b^2).
3. Replace "a" with 3x and "b" with 1 in the formula.
(3x)^3 - 1^3 = (3x - 1)((3x)^2 + (3x)(1) + 1^2)
4. Simplify the expression inside the parentheses.
(3x - 1)(9x^2 + 3x + 1)
Therefore, using the difference of cubes formula, we can factor 27x^3 - 1 as (3x - 1)(9x^2 + 3x + 1).
Step-by-step explanation:
b.(–3, 49)
c.(3, 25) and (7, 9)
d.(–3, 49) and (–7, 65)
Answer: c.(3, 25) and (7, 9)
y = –x^2 + 6x + 16 and y = –4x + 37
Plug in -4x+37 for y in first equation . It becomes
Combine like terms. add 4x and subtract 37 on both sides
Divide the whole equation by -1 to remove negative sign from -x^2
Now factor the left hand side
(x-7)(x-3) = 0
x-7 =0 and x-3=0
x= 7 and x=3
Now we find out y using y = –4x + 37
when x= 7 , then y=-4(7) +37 = 9
when x= 3, then y=-4(3) + 37 = 25
We write solution set as (x,y)
(7,9) and (3,25) is our solution set
Ax + B = C
Answer:
(C - B)/A = x
Step-by-step explanation:
Ax + B = C
-B -B
Ax = C - B
Divide both sides by A
x = (C - B)/A
(C - B)/A = x